The Influence of School Image on Students Satisfaction After Getting Academic Service in High School - Mubarok, Sasongko Irham; Sutarto, Joko; Muhsin, Muhsin (Educational Management, 2020)
The purpose of this study was to describe and analyze the effect of school image on students' satisfaction after obtaining academic services at SMA NASIMA Semarang. The approach used in this study is a quantitative approach using path analysis, the population in the study amounted to 154 students with a sample of 111 students. The sampling technique used in this study was Proportionate Stratified Random Sampling. The results of this study, namely, school image have a significant effect on student satisfaction. School image has a significant effect on academic services. Academic has a significant effect on students' satisfaction. School image has a significant effect on students' satisfaction after being mediated by academic services.